(untitled) (Archives of Pediatrics of Uruguay, 2023)
Moebius syndrome is a rare congenital disease characterized by unilateral or bilateral involvement of the VI and VII cranial nerves, which compromises the muscles that control ocular motricity with paralysis in the abduction of the eyeball and the muscles involved in the facial expression. Its clinical presentation and degrees of severity are variable, and it can be symmetric or asymmetric. Additionally, most of the cases are related to language disorders, musculoskeletal and orofacial anomalies. This paper presents the case of a 3-year-old female patient, product of a trigemellar pregnancy with a clinical diagnosis of Moebius syndrome at birth, confirmed by neuroimaging, which shows the bilateral absence of the facial nerve in point-lateral angles. Additionally she has a complete defect in abduction and adduction eye movements, which prevents the common convergent strabismus in these patients.